Pengaruh Celebrity Endorser Dan Brand Image Terhadap Keputusan Pembelian Produk Focallure Dengan Kepercayaan Sebagai Variabel Intervening: Studi Kasus Masyarakat Jl. Kancil Dusun 1 Sei Rampah - Rusmewahni, Rusmewahni; Hartanto, Bobby; Triandani, Mulya; Effendy, Yudi (Management And Business Progress, 2025)
This research aims to find out how Celebrity Endorser and Brand Image influences Focallure Product Purchasing Decisions with trust as an intervening variable. The influences you want to know are direct and indirect influences. This type of research is quantitative research which describes the location of the variables studied and the influence of one variable on other variables. The population of this study was taken from community of Jl. Kancil village 1 Sei Rampah, specifically women. The sample taken was 92 respondents using the Slovin formula with the Accidental Sampling technique. The data analysis method uses PLS-based SEM, analyzed using outer models, inner models, and hypothesis testing using bootstrapping. The results of this research show that : Celebrity Endorser influences Purchasing Decisions, Brand Image influence Purchasing Decisions, Celebrity Endorser influences trust, Brand Image influences trust, Trust has no effect on Purchasing Decisions, Celebrity Endorser does not have a significant influences on Purchasing Decisionswith trust as an intervening variable, Brand Image does not have a significant influences on Purchasing Decisionswith trust as an intervening variable.